Sympatric breeding occurrence of two call types of Evening Grosbeak in Western Wyoming - Duman, Konshau W.; Hahn, Thomas P. (Frontiers in Bird Science, 2024)
The Evening Grosbeak (Coccothraustes vesperitinus Cooper, 1825) is a species with multiple vocally distinct recognized groups known as call types. The range boundaries and degrees of overlap between these groups remain an area of continuing research. We report sympatric breeding occurrence of Evening Grosbeaks of call type 1 and call type 4 in the Jackson Hole area of Wyoming, and we show that these two call types have been overlapping in this region for at least 24 years. We also note a major increase in the local abundance of Evening Grosbeaks in 2023 compared to past years. These findings suggest that the range boundary between these two call types is relatively consistent at this short time scale, but it may fluctuate somewhat given changes in the proportions of the two types over this period. We detected both call types continuously through the 2023 breeding period in the Jackson Hole area, and we had breeding season detections of both types in the area in 2000, 2005, 2006, 2007, 2008, 2010, and 2012. In 2023, a majority were the Pacific Northwest-centered type 1 while roughly a quarter were type 4 which is known from the Central Rockies. In 2023, we generally saw type 4 individuals alongside type 1 individuals, and both call types tended to cluster in the same areas though type 1 birds were frequently detected without any type 4s nearby. We most frequently encountered both types in Douglas Fir (Pseudotsuga menziesii Mirb. Franco) or Subalpine Fir (Abies lasiocarpa (Hook.) Nutt.) dominated forests through the June–July breeding season, and both were abundant in areas with Chokecherry (Prunus virginiana L.) or Serviceberry (Amelanchier alnifolia (Nutt.) Nutt. Ex M.Roem.) after the breeding season. Despite considerable survey effort, we could not detect either type north of Moran, WY. Describing this close overlap of call types with uncertain taxonomic status paves the way for further research investigating the potential for ecological and genetic isolation of the two groups in areas where mixed parentage is most possible.